CpG Islands Shape the Epigenome Landscape. Issue 6 (19th March 2021) - Papin, Christophe; Le Gras, Stéphanie; Ibrahim, Abdulkhaleg; Salem, Hatem; Karimi, Mohammad Mahdi; Stoll, Isabelle; Ugrinova, Iva; Schröder, Maria; Fontaine-Pelletier, Emeline; Omran, Ziad; Bronner, Christian; Dimitrov, Stefan; et al.
Abstract: Epigenetic modifications and nucleosome positioning play an important role in modulating gene expression. However, how the patterns of epigenetic modifications and nucleosome positioning are established around promoters is not well understood. Here, we have addressed these questions in a series of genome-wide experiments coupled to a novel bioinformatic analysis approach. Our data reveal a clear correlation between CpG density, promoter activity and accumulation of active or repressive histone marks. CGI boundaries define the chromatin promoter regions that will be epigenetically modified. CpG-rich promoters are targeted by histone modifications and histone variants, while CpG-poor promoters are regulated by DNA methylation. CGIs boundaries, but not transcriptional activity, are essential determinants of H2A.Z positioning in vicinity of the promoters, suggesting that the presence of H2A.Z is not related to transcriptional control. Accordingly, H2A.Z depletion has no impact on gene expression of arrested mouse embryonic fibroblasts. Therefore, the underlying DNA sequence, the promoter CpG density and, to a lesser extent, transcriptional activity, are key factors implicated in promoter chromatin architecture. Graphical abstract: Unlabelled Image Highlights: CpG-rich tracks are a highly conserved feature of vertebrate promoters. CGIs define the genome-wide pattern of nucleosome positioning in vicinity of promoters. CGIs dictate the histone code at promoters. H2A.Z does not regulate transcription in arrested fibroblasts. H2A.Z nucleosome positioning at promoters is related to CGIs.